Islamic Economic Justice and Governance: Pathways to Human Development in Developing Muslim Majority Countries - Basri, Basri; Herianti, Herianti; Eally Earizza Binti Moksin (El-Qish: Journal of Islamic Economics, 2025)
This study aims to investigate how governance influences the Human Development Index (HDI) in eight developing Muslim-majority countries, collectively known as the D-8, by integrating an Islamic economic perspective. While existing literature recognizes governance as a key driver of HDI, few studies explore how Islamic economic values interact with governance mechanisms to shape human development outcomes. This research addresses this gap by examining the relationships among governance indicators, Islamic financial development, and HDI performance. Utilizing panel data from D-8 countries covering the period from 2013 to 2023, we employ the Generalized Method of Moments (GMM) approach to analyze the interactions between governance quality, Islamic financial development, and human development. Governance is assessed through indicators such as government effectiveness, regulatory quality, and control of corruption, while Islamic financial development is measured by the growth and outreach of Shariah-compliant financial institutions. Our findings reveal three key insights: (1) Governance exerts a synergistic effect that enhances HDI in D-8 countries. (2) The impact of individual governance indicators varies, with government effectiveness and regulatory quality consistently associated with higher HDI. (3) Islamic financial development positively influences HDI, particularly in health and social welfare sectors, underscoring the role of Islamic values in promoting human well-being. This study contributes to the economic development literature by demonstrating how Islamic economic principles can support the achievement of Sustainable Development Goals (SDGs) within a robust governance framework. For policymakers, the findings highlight the importance of aligning Islamic welfare principles with governance reforms to optimize human development outcomes in developing Muslim-majority countries.